(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the relevance of the pedagogical process aimed at achieving physical maturity, the importance of mental, moral, aesthetic and labor education in the process of physical education, the development of the professional competence of physical education teachers by improving the system of training future personnel, updating their knowledge and skills, the issues of adaptation to requirements, development of worldview and expansion of thinking are analyzed.